Anal ultrasound in the diagnosis of anal carcinoma - Sudoł-Szopińska, Iwona (Radiology and oncology (Ljubljana), 2001)
Background. We present a case of adenocarcinoma of the anal canal to demonstrate the usefulness of the anal ultrasound (AUS) in the diagnostics. Case report. AUS was performed with the use of Bruel and Kjaer scanner type 3535 with an axial 7.0 MHz endnprobe. Examination was performed in left lateral position. AUS allowed for exact assessment of the depth of infiltration of the anal wall by the tumor, and precisely visualized its location and echotexture. Assessment of the perianal lymph nodes and tumor spread into adjacent tissues was also possible. Conclusions. AUS is a valuableimaging method in assessing the depth of invasion of anal carcinoma and gives valuable information before deciding on the choice of treatment.
Keywords: Adenocarcinoma; Adenokarcinom; Aged; anus; Anus neoplasms; Anus, novotvorbe; diagnostika; Ostareli; radiološka diagnostika; rak (medicina); Ultrasonography